2009
DOI: 10.21432/t2630w
|View full text |Cite
|
Sign up to set email alerts
|

Encouraging self-regulated learning through electronic portfolios

Abstract: At the Centre for the Study of Learning and Performance (CSLP) at Concordia University in Montreal, Quebec, we have developed the Electronic Portfolio Encouraging Active Reflective Learning Software (ePEARL) to promote student self-regulation and enhance student core competencies. This paper summarizes the literature on electronic portfolios (EPs), describes ePEARL, and documents our research findings to date including analyses of teacher and student reactions. Participants in this study were 62 school teacher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
7

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 14 publications
1
36
0
7
Order By: Relevance
“…These results follow the lines of other studies (Abrami et al, 2008;Galy, Downey, & Johnson, 2011;Jafari & Kaufman, 2006). In a study summarized by Jafari and Kaufman (2006), the goal of which was to assess digital competency development over a threemonth period and to examine pre-service teachers' perception of the electronic portfolio as a learning tool, the results show that pre-service teachers' technological competencies increased while they worked on the electronic portfolio and that they responded favourably to the electronic portfolio as a learning tool.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These results follow the lines of other studies (Abrami et al, 2008;Galy, Downey, & Johnson, 2011;Jafari & Kaufman, 2006). In a study summarized by Jafari and Kaufman (2006), the goal of which was to assess digital competency development over a threemonth period and to examine pre-service teachers' perception of the electronic portfolio as a learning tool, the results show that pre-service teachers' technological competencies increased while they worked on the electronic portfolio and that they responded favourably to the electronic portfolio as a learning tool.…”
Section: Discussionsupporting
confidence: 93%
“…For example, self-regulated learning (SRL) has been studied in association with this technology (Abrami, Wade, Pillay, Aslan, Bures, & Bentley, 2008), specifically the relationship between students' SRL ability and e-portfolio achievement in a language enhancement programme (Cheng & Chau, 2013). In another attempt to understand the student's perspective, the study by Lopez-Fernandez and Rodriguez-Illera (2009) applied a mixed-method analysis to analyse the impact of this technological innovation on students and their satisfaction.…”
Section: The Importance Of University Students' Perspectivementioning
confidence: 99%
“…With proper guidance, students valued the opportunity for reflection and engaged in critical reflective examination of their learning growth, connecting theories with practices, and realising their achievement of important competencies. Goal orientation has been suggested as an important step in learning (Abrami et al, 2008) and found to impact learners' reflective ability demonstrated in their e-portfolios (Cheng & Chau, 2013). From a goal setting perspective, the reflection instruction seems to sufficiently help learners understand and set a goal of reflection to demonstrate their growth in TPACK instead of in other aspects.…”
Section: Discussionmentioning
confidence: 99%
“…Wade, Abrami and Sclater (2008) break this into metacognitive selfregulation, physical and social environment management, time management and effort regulation relating to achieving goals. Abrami et al (2009) suggest three cyclical phases of self-regulation: 'forethought', that is, planning and goal setting; 'performance', that is, self observation; and 'self-reflection'.…”
Section: Theoretical Frameworkmentioning
confidence: 99%